Analisis Bibliometrik: Tren Penelitian Hubungan Kemampuan Berpikir Kiritis terhadap Kesadaran Lingkungan pada Pembelajaran IPA - Sri Rejeki Dwi Astuti; Soraya Firdausi; Sri Wahyuni (ScienceEdu, 2023)
This research purposed to analyze the research trend on the relationship between critical thinking abilities and environmental awareness in science learning based on bibliometric analysis. The research method is a literature review with a bibliometric analysis approach to analyze journal articles indexed in Scopus and Google Scholar. It conducted through five stages, including data collection, keyword selection, creating relationship matrices, visualizing results, and interpreting data and visualization results. Data retrieval utilized the Publish or Perish 8 software. Data analysis was conducted using VOSViewer. The research results indicate that trend of research on the relationship between critical thinking abilities and environmental awareness in science learning over the past 8 years (2019-2023) based on the Scopus and Google Scholar databases consists of 5 clusters, with students as the dominant subject of the research. Bibliometric data shows that in 2023, there will be no publications indexed in Scopus or Google Scholar that discuss the relationship between critical thinking abilities and environmental awareness among students in science learning.